Implementation Of Influencer Marketing And Customer Experience In Improving Consumer Purchase Decisions In Tembaga Seafood Medan - Situmorang, Irvan Rolyesh; Gultom, Pesta; Dovean, Dovean (UNIVERSITAS PAKUAN, 2025)
This study aims to determine the effect of influencer marketing and customer experience on consumer purchasing decisions at Tembaga Seafood Medan. The background of the study is based on fluctuations in the number of consumers and business income which are thought to be influenced by marketing strategies through social media and consumer experiences when interacting with products and services. This study uses a quantitative method with a descriptive approach. A sample of 130 respondents was determined using incidental sampling techniques, with data collection through questionnaires, observations, and documentation. Data analysis techniques include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and t-tests and F-tests. The results of the study indicate that partially influencer marketing has a significant effect on consumer purchasing decisions. Likewise, customer experience has a significant effect on purchasing decisions. Simultaneously, influencer marketing and customer experience have a significant effect on consumer purchasing decisions at Tembaga Seafood Medan. These findings indicate that promotional strategies through social media and improving the quality of customer experience play an important role in driving consumer purchasing decisions.